Selfless or Selfish? The impact of message framing and egoistic motivation on narcissists’ compliance with preventive health behaviors during COVID-19 - Tobias Otterbring (Elsevier, 2021)
COVID-19 is one of the greatest international health crises in recent years. Due to the highly contagious nature of the virus, the World Health Organization has recommended that people comply with a set of preventive measures to reduce the infection rate (e.g., social distancing, wearing a face mask, thorough personal hygiene). However, people typically differ in the extent to which they are willing to comply with such recommendations, as they imply certain personal restrictions. The present study aimed to investigate whether narcissism levels and message framing strategies affect individuals’ willingness to accept personal restrictions and, consequently, comply with a set of preventive health behaviors. Results reveal that people high (vs. low) in grandiose narcissism are less likely to accept personal restrictions and comply with preventive health behaviors, with negative (vs. positive) message framing constituting a more effective strategy for convincing such individuals to comply with said restrictions and behaviors. This effect can be explained through a more pronounced willingness of participants high in grandiose narcissism to accept personal restrictions to protect themselves (egoistic motivation) but not through a willingness to protect vulnerable people (altruistic motivation). Our findings suggest that individuals who remain uncooperative during pandemics could be more effectively addressed with adapted message framing strategies and incentives tailor-made for their distinct personalities.